The Influence of Digial Payment Quick Response Code Indonesian Standard (QRIS) and Lifestyle on Consumptive Behaviour of Students in Banda Aceh - Arifin, Muhammad; Meutia, Rachmi; Salsabila, Cut Sarah Athiyah (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2025)
The use of digital payment QRIS can influence individual's purchasing decisions and even lead to consumptive behavior due to the ease and convenience of daily transactions. Additionally, lifestyle is also a factor that can affect consumptive behavior, especially when in a high-living environment. This study aims to determine the impact of QRIS usage and lifestyle on the consumptive behavior of students in Banda Aceh. This research is quantitative, involving 100 student respondents in Banda Aceh. The results indicate that QRIS does not significantly affect the consumptive behavior, while the lifestyle variable has a positive and significant impact on the consumptive behavior of students in Banda Aceh. Although digital payment QRIS provides ease and practicality for transactions, student’s purchasing behavior in Banda Aceh remains manageable and does not lead to excessive consumption. In contrast, the lifestyle of students in Banda Aceh has a strong influence on how they manage their spending and consumption, leading to consumptive behavior among these students.